Molecular studies on E.coli isolate from milk of mastatic cattle with special reference to associated biochemical changes in kaliobea governorate - Radwan, Mervat E.I.; Abo-Zaid, Khiary Farouk (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
This investigation was performed in Teaching hospital and farm of Benha university in Moshtohor the number of cows in this farm 80 dairy cows that 40 of them had clinical signs of mastitis (inflammation in teats ,pain in milking and milk decrease in amount and quality) .When examine these cows to identify the disease which cause these signs . California Mastitis Test (CMT) was performed to determine positive milk samples in the Mastitic targeted cows. 20 samples of early lactation stage cows out of 40 samples recovered from CMT- positive milk samples. Biochemical and PCR tests were performed to isolates E. Coli from positive milk samples (CMT) and determined three virulance genes, eae gene ,SXT1 and SXT2 . The significance of Escherichia coli-induced mastitis and biochemical changes associated to it in cows, due to the presence of virulence genes and wide range resistance to 20 antimicrobials, is concluded. E.coli cause biochemical changes in mastatic cow as (liver enzymes AST,GPT,TP, ant. oxidative enzymes as CAT, SOD,GST,LDand kidney function as urea and creatinine .E.coli has effect on inflammatory response in immunity system of mastitic cow by increase IL6,TNF and CRP.